VITAMIN D RECEPTOR GENE Bsmi SINGLE NUCLEOTIDE POLYMORPHISM IN THE PATIENTS WITH ACUTE DISORDERS OF CEREBRAL CIRCULATION - Obukhova, O.A.; Garbuzova, V.Yu.; Ataman, Y.A.; Budko, V.V.; Ataman, A.V. (World of Medicine and Biology, 2012)
BsmI polymorphism (rs1544410) of vitamin D receptor (VDR) gene in 170 patients with ischemic atherothrombotic stroke (IATS) and in 124 healthy people was determined. It was shown that in the patients with IATS distribution of b/b homozygotes, heterozygotes and B/B homozygotes was 41,8%, 43,5% and 14,7% (in control – 46%, 41,9% and 12,1%, P=0,707 by χ2-test). In the individuals both of female and male sex any statistically significant association between the BsmI polymorphism of the VDR gene and IATS was not revealed.
Keywords: vitamin D receptor; gene polymorphism; ischemic stroke